PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN (STUDI PADA KEDAI KOPI KINI SUKARAME) - Firmanto, Ahmad; Arrasyid, Alfin; Agusti, Devimeylinda (Journal for Management Student (JFMS), 2023)
Product quality and price perception are two main factors that influence customer loyalty in a business. High product quality tends to increase customer satisfaction and build long-term relationships between products and consumers. Meanwhile, perceptions of price or relative value of products can influence how customers assess fairness in the exchange between what they pay and what they receive. This research aims to determine the relationship between product quality and price perception on consumer loyalty. This research uses a quantitative approach. The data used is primary data by distributing questionnaires online via Google Form. The population in this research is current Sukarame coffee shop consumers. The sample used was 91 respondents and was taken using non-probability sampling using accidental sampling technique. With the help of the SmartPLS4 test tool. The results of this research show that: (1) Product quality (X1) has a positive and significant effect on customer loyalty (Y) so it can be concluded that the hypothesis is accepted. (2) Price perception (X2) has a positive and significant effect on customer loyalty (Y), it can be concluded that the hypothesis is accepted.